On-line control of light intensity in a microalgal bioreactor using a novel automatic system - Meireles, Luís A. (2010)
The influence of light intensity upon biomass and fatty acid productivity by the microalga Pavlova lutheri was experimentally studied using a novel device. This device was designed to automatically adjust light intensity in a photobioreactor: it takes on-line measurements of biomass concentration, and was successfully tested to implement a feedback control of light based on the growth rate variation. Using said device, batch and semicontinuous cultures of P. lutheri were maintained at maximum growth rates and biomass productivities – hence avoiding photoinhibition, and consequent waste of radiant energy. Several cultures were run with said device, and their performances were compared with those of control cultures submitted to constant light intensity; the biomass levels attained, as well as the yields of eicosapentaenoic and docosahexaenoic acids were calculated – and were consistently higher than those of their uncontrolled counterpart.